Electrical Characterization of Thin Layer Materials: Destructive and Non-Destructive Irreversible Processes in Langmuir Films - Drahoslav Barancok; Julius Cirak; Pavol Tomcik; Jan Vajda; Martin Weis (Communications - Scientific letters of the University of Zilina, 2006)
Summary Well-defined Langmuir-Blodgett films prepared by reproducible technique are still highly attractive for exploitation in investigation of subjects as diverse as chain packing, phase transitions, two-dimensional physics, biosensors and membrane physics. During last 15 years the Maxwell displacement current (MDC) measuring technique was developed for dynamic study of monolayers. In experiment MDC flows through the metal electrode/air gap/Langmuir monolayer/water surface structure. Spontaneous formation of the monolayer was observed and significant differences between destructive and non-destructive processes are discussed.